Environmental Impact Analysis Application Of Environmental Systems Models In The Georgetown-Butterworth Chanel Zone - Chan, Huan Chiang (1979)
The matrix is used by checking each action that is likely to be involved significantly in a particular human activity by making a slash diagonally from the top right to the bottom left of the appropriate cells. The upper left hand corner is used to indicate the magnitude of impact by a value from 1-10. Similarly the lower right corner is used to indicate the importance of the impact also ty a value from 1-10.